Hate crimes and normative regulation - Kovačević Milica (Temida)
This paper is primarily devoted to issues related to the normative regulation of hate crimes, with special reference to the regulations of the Republic of Serbia, which are indirectly related to this matter. This kind of crimes are characterized by prejudices that perpetrators have towards injured parties, as members of certain, mostly, minority groups, due to which many hate crimes could be also called crimes of prejudice. In comparative law there are two different basic directions when it comes to regulating hate crimes: separation of hate crimes in a separate category on the one hand, and punishment of perpetrators of criminal acts with the detriment of minority groups through the usual charges of a given criminal justice system, on the other. The author finds that, regardless of the formal response forms, real life suggests that hate crimes can be essentially suppressed only by promoting values such as equality, respect for diversity and tolerance, and by continuous education of public about the danger of hate crimes.